Transgenic overexpression of glutathione S-transferase μ-type 1 reduces hypertension and oxidative stress in the stroke-prone spontaneously hypertensive rat - Olson, Erin; Pravenec, Michal; Landa, Vladimir; Koh-Tan, H H Caline; Dominiczak, Anna F; McBride, Martin W; Graham, Delyth (Journal of hypertension, 2019)
BACKGROUND: Combined congenic breeding and microarray gene expression profiling previously identified glutathione S-transferase μ-type 1 (Gstm1) as a positional and functional candidate gene for blood pressure (BP) regulation in the stroke-prone spontaneously hypertensive (SHRSP) rat. Renal Gstm1 expression in SHRSP rats is significantly reduced when compared with normotensive Wistar Kyoto (WKY) rats. As Gstm1 plays an important role in the secondary defence against oxidative stress, significantly lower expression levels may be functionally relevant in the development of hypertension. The aim of this study was to investigate the role of Gstm1 in BP regulation and oxidative stress by transgenic overexpression of the Gstm1 gene. METHOD: Two independent Gstm1 transgenic SHRSP lines were generated by microinjecting SHRSP embryos with a linear construct controlled by the EF-1α promoter encoding WKY Gstm1 cDNA [SHRSP-Tg(Gstm1)1 and SHRSP-Tg(Gstm1)2]. RESULTS: Transgenic rats exhibit significantly reduced BP and pulse pressure when compared with SHRSP [systolic: SHRSP 205.2 ± 3.7 mmHg vs. SHRSP-Tg(Gstm1)1 175.5 ± 1.6 mmHg and SHRSP-Tg(Gstm1)2 172 ± 3.2 mmHg, P < 0.001; pulse pressure: SHRSP 58.4 ± 0.73 mmHg vs. SHRSP-Tg(Gstm1)1 52.7 ± 0.19 mmHg and SHRSP-Tg(Gstm1)2 40.7 ± 0.53 mmHg, P < 0.001]. Total renal and aortic Gstm1 expression in transgenic animals was significantly increased compared with SHRSP [renal relative quantification (RQ): SHRSP-Tg(Gstm1)1 1.95 vs. SHRSP 1.0, P < 0.01; aorta RQ: SHRSP-Tg(Gstm1)1 2.8 vs. SHRSP 1.0, P < 0.05]. Renal lipid peroxidation (malondialdehyde: protein) and oxidized : reduced glutathione ratio levels were significantly reduced in both transgenic lines when compared with SHRSP [malondialdehyde: SHRSP 0.04 ± 0.009 μmol/l vs. SHRSP-Tg(Gstm1)1 0.024 ± 0.002 μmol/l and SHRSP-Tg(Gstm1)2 0.021 ± 0.002 μmol/l; (oxidized : reduced glutathione ratio): SHRSP 5.19 ± 2.26 μmol/l vs. SHRSP-Tg(Gstm1)1 0.17 ± 0.11 μmol/l and SHRSP-Tg(Gstm1)2 0.47 ± 0.22 μmol/l]. Transgenic SHRSP rats containing the WKY Gstm1 gene demonstrate significantly lower BP, reduced oxidative stress and improved levels of renal Gstm1 expression. CONCLUSION: These data support the hypothesis that reduced renal Gstm1 plays a role in the development of hypertension.
Keywords: Oxidative Stress; aorta; oxidační stres; Systole; Malondialdehyde; potkani transgenní; Hypertension; geneticky modifikovaná zvířata; ledviny; Rats, Inbred WKY; peroxidace lipidů; Kidney; krysa rodu Rattus; zvířata; Rats, Transgenic; Glutathione; Glutathione Transferase; potkani inbrední WKY; Animals, Genetically Modified; krevní tlak; Male; potkani inbrední SHR; hypertenze; glutathion; Rats; Animals; systola; mužské pohlaví; Aorta; glutathiontransferasa; Blood Pressure; malondialdehyd; Rats, Inbred SHR; Lipid Peroxidation